Role of personality in scientific advancement (dedicated to the eightieth anniversary of the birth of Lev G. Gassanov) - Glushechenko, E. M.; Narytnik, T. N. (Technology and design in electronic equipment, 2016)
The article is dedicated to Lev G. Gassanov who between 1974 and 1991 headed the "Saturn" Research Institute. Lev Gassanov was an outstanding personality, a talented leader, organizer and scholar, author of many books, scientific works and inventions, he founded a national school for the creation of a broad range of micropower electronics devices and systems.